Economical and technical aspects of producing of diamond impregnated tools - Borowiecka-Jamrozek, Joanna; Lachowski, Jan (Univerzita Pardubice, 2013)
In the paper the analysis of dynamics of mining, production and prices of industrial diamonds and cobalt was performed during 1900-2011 years. Cobalt is using as a based material used for matrix of diamond impregnated tools for cutting of natural stones. Until the early 1950s the developments in diamond tools were relatively slow. In that period only mined diamond crystals were available. Much faster developments in the tool manufacturing technology was caused by development the production of synthetic diamonds. Only the possibility of producing synthetic diamond allowed for controlled modification of the shape and properties of particles, from very finegrained, used for grinding and polishing, to large, strong crystals of the regular, multifaceted shape. In the new millennium the market for diamond tools continues to grow rapidly. The effective use of diamond impregnated tools is strongly depended on the retentive properties of the metal matrix, which must hold diamond grits firmly. The diamond retentive capability in a matrix is a complex property, affected mainly by chemical or mechanical interactions during hot pressing and then cooled to room temperature. Due to mismatch between thermal expansion coefficients of the matrix and diamond, the stress/strain field is generated in the matrix at diamond surroundings, which plays a major role when retentive properties are considered. The potential retentive capability of a matrix can be associated with the amount of elastic and plastic deformation energy and the size of a deformated zone which occurs in the matrix around diamond particles. The costs of producing diamond impregnated tools are influenced by the costs of cobalt metallic matrix. After World War II the price of cobalt further fluctuated on a balanced level, until the mid 1970s when the price increased rapidly The possibility of substitution of cobalt with the other cheaper alloys was considered which as a matrix material gives similar utilizing properties.
Keywords: cobalt; industrial diamonds; sinters; metallic matrix; diamond impregnated tools